Effect of feeding sorghum stover treated with Rabaa ash alkali on digestibility and performance of Nubian goats - Hamed, Asma Himmed; Elimam, Mohamed (Gezira Journal of Agricultural Science; Vol 8 No 1 (2010), 2010)
Ash from some plants in the Sudan was evaluated for alkalinity and used in upgrading straws since it is cheap and safe. Alkalinity varied greatly among plant species and was highest for Rabaa ( Trianthema pentandra L. ) and least in Buda (Striga hermonthica (Del) Benth.). Effects of Rabaa ash alkali on chopped sorghum stover (Tabat variety) dry matter and water intakes, digestibility and body weight changes in Nubian goats were studied. Sorghum stover was treated with 0%, 3%, 5% and 8% Rabaa ash solutions forming diet US, AT 1 S, AT 2 S and AT 3 S, respectively. The alkali significantly (p<0.05) depressed dry matter intake (DMI) compared to untreated stover and the effect was 839, 688, 619 and 661 g/day for US, AT 1 S, AT 2 S and AT 3 S, respectively. Water intake was 3303, 4164, 3752 and 3264 ml/day for US, AT 1 S, AT 2 S and AT 3 S, respectively. The alkali increased DM, OM, CP, EE and CF apparent digestibilities and the effects were increased with alkali level. A non- significant weight gain was noticed in all treatments. تم تقييم قلوية رماد بعض النباتات بالسودان لاستخدامها في تحسين الاتبان لأنه رخيص ومأمون. تختلف القلوية في النباتات المختلفة. وجد أعلى قيمة قلوية في نبات الربعة وأقل قيمة في نبات البودا. تمت دراسة تأثير قلوي رماد الربعة على استهلاك المادة الجافة والماء والهضمية الظاهرية والتغير في الوزن في الماعز النوبي. تمت معاملة تبن الذرة بمستويات  0و 3 % و 5  % و8 % من محلول رماد نبات الربعة مكونا ِ   AT3S  ,AT2S  ,AT1S ,US على التوالي. أدى القلوي إلى انخفاض معنوي للمادة الجافة المتناولة  مقارنة بغير المعامل وكان الاثر839 و 688 و 619 و661 جرام /اليوم لكل من  USوAT1S  وAT2S و AT3S على التوالي. كان استهلاك الماء 3303 و 4164 و3752 و 3264 مل/اليوم لكل من  USوAT1S  وAT2S و AT3S على التوالي. أدى القلوي إلى زيادة الهضمية الظاهرية للمادة الجافة والمادة العضوية والبروتين الخام والدهن الخام والألياف الخام وازداد التأثير بازدياد مستوى القلوية. تلاحظ أن هناك زيادة غير معنوية في الوزن في كل المعاملات.